Isolation of β-glucan from Eleusine coracana and its antibiofilm, antidiabetic, antioxidant, and biocompatible activities. (March 2020) - Divya, Mani; Karthikeyan, Sivashanmugam; Ravi, Cyril; Govindarajan, Marimuthu; Alharbi, Naiyf S.; Kadaikunnan, Shine; Khaled, Jamal M.; Almanaa, Taghreed N.; Vaseeharan, Baskaralingam
Abstract: Eleusine coracana (Finger millet) has high nutritional value with numerous health benefits and is of low cost. Isolation of beta-glucan ( βG ) from E. coracana ( Ec-βG ) has gained increasing research attention. UV–vis spectroscopy used to measure the surface plasmon resonance at 361 nm to confirm the presence of polysaccharides (glucan molecules) in Ec-βG . X-ray diffraction analysis of Ec-βG displayed a crystalline nature and confirmed the presence of the βG molecule. Further, the bioactive compounds of Ec-βG were screened using gas chromatography-mass spectrometry. The antibacterial activity of Ec-βG against both Gram-positive ( Lysinibacillus fusiformis, Enterococcus faecalis ) and Gram-negative ( Proteus vulgaris, Shigella sonnei ) bacteria were assessed through minimum inhibitory concentrations <70 μg/ml of Ec-βG. In addition, the antibiofilm activity and bacterial viability of Ec-βG at 100 μg/ml was confirmed by light and confocal laser scanning microscopy. Furthermore, Ec-βG inhibits α-amylase and α-glucosidase at an IC50 -value of 1.23 and 1.42 μg/ml, respectively. Superoxide anion scavenging activity at IC50 -1.4 μg/ml and DPPH radical scavenging activity at IC50- 1.2 μg/ml showed that Ec-βG had potential antioxidant property. The in vitro hemolysis assay for biocompatibility of Ec-βG at 200 μg/ml showed 0.06 ± 0.09%. Therefore, Ec-βG has the potential to act as a suggestive agent for antibacterial, antidiabetic, and antioxidant activity. Graphical abstract: Image 1 Highlights: Betaglucan ( βG ) was isolated from Eleusine coracana ( Ec ) seeds and characterized with UV–vis. spectrum, XRD, and GC-MS. Ec-βG exhibits antibiofilm activity against L. fusiformis, E. faecalis, P. vulgaris and S. sonnei at 100 μg/ml. Ec-βG was found to be an active inhibitor for α-amylase and α-glucosidase that demonstrates antidiabetic activity. Maximum concentration (200 μg/ml) of Ec-βG has the lowest hemolysis percentage which shows its biocompatibility.